The Potential of Artificial Intelligence in Addressing Climate Change - Szeberényi, András; Kovács, Imre Mátyás; Fűrész, Ágnes (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Artificial intelligence (AI) has become an instrumental technology in the fight against climate change, especially in industrial and corporate settings. This study specifically explores how businesses within the facilities management sector have integrated AI technologies to mitigate and adapt to climate challenges. Four expert interviews with corporate leaders who have successfully deployed AI solutions were conducted to identify key challenges, barriers, and success factors in implementing AI-driven climate solutions, and develop recommendations for businesses seeking to leverage AI for climate action. The findings of this study highlight the significant potential of AI in addressing climate change challenges within the facilities management sector, including demand response management, predictive maintenance, smart building optimization, and supply chain decarbonization. Demand response management has effectively reduced peak load stress and significantly lowered annual CO2 emissions, while predictive maintenance has contributed to a noticeable reduction in energy waste and an extension of machinery lifespan. Key results include the substantial environmental benefits achieved through targeted AI interventions in energy management and the risk mitigation gained from gradual implementation strategies.